A.M.S. exhibition of African paintings (International Library of African Music, 1958)
Two years ago, the Society acquired over 70 representative pictures from the two groups of painters at Brazzaville and Elizabethvilie and with the co-operation of two Johannesburg Clubs for African boys and girls, framed and equipped the pictures for permanent exhibition around the country. Up till that moment few people in the southern end of the Continent had had the opportunity of seeing any representative collections of original African paintings, the public having to be content and not very impressed with ‘schooled’ paintings in styles adopted directly from Europeans.
Keywords: African Music